Cutting Costs to Live Within Your Income - Josephine Turner; Michael S. Gutter; Nayda I. Torres (EDIS)
Developing self-control of your spending is a basic step in cutting the cost of living. Some families are able to afford what they want, even on a limited income. This may result from having more experience or greater skills. You probably know specific things you could do to reduce spending. These suggestions may work for you. This revised 3-page fact sheet was written by Josephine Turner, Michael S. Gutter, and Nayda I. Torres, and published by the UF Department of Family, Youth and Community Sciences, October 2012.